Representatividade das mulheres nos Legislativos Estaduais no período de 2010 a 2020 - (:unkn) unknown (Universidade Federal do Pampa, 2025)
This study analyzes female participation in Brazilian State Legislative Assemblies, highlighting the main challenges women face in politics. The research, qualitative and descriptive in nature, was based on bibliographic and documentary analysis, as well as official data. Despite being the majority of the population and electorate, women still occupy a small percentage of political positions. Gender quotas and public funding for female candidates represent important progress but remain insufficient given the structural and cultural barriers and the prevalence of political gender-based violence. The study also reveals that party control over financial resources and the lack of effective support hinder women’s electoral success. It concludes that it is necessary to go beyond quotas, implementing public policies and affirmative actions that ensure greater equity and strengthen democracy.
Representation of women in State Legislatures from 2010 to 2020
Keywords: Mulheres na política; Representatividade feminina; Violência política; Ciencia política; Women in politics; Female representation; Political violence; Political science; CIENCIAS SOCIAIS APLICADAS